Clinical Impact of Plasma and Tissue Next‐Generation Sequencing in Advanced Non‐Small Cell Lung Cancer: A Real‐World Experience. (7th July 2020) - Bonanno, Laura; Pavan, Alberto; Ferro, Alessandra; Calvetti, Lorenzo; Frega, Stefano; Pasello, Giulia; Aprile, Giuseppe; Guarneri, Valentina; Conte, PierFranco; ,
Abstract: Background: Targeted agents have improved the outcome of a subset of non‐small cell lung cancer (NSCLC). Molecular profiling by next‐generation sequencing (NGS) allows screening for multiple genetic alterations both in tissue and in plasma, but limited data are available concerning its feasibility and impact in real‐world clinical practice. Methods: Patients with advanced NSCLC consecutively referring to our Institution for potential eligibility to VISION trial (NCT02864992) were prospectively enrolled. They were already screened with standard method, and EGFR/ALK/ROS‐1 positive cases were excluded. NGS was performed in plasma and tissue using the Guardant360 test covering 73 genes and the Oncomine Focus Assay covering 59 genes, respectively. Results: The study included 235 patients. NGS was performed in plasma in 209 (88.9%) cases; 78 of these (37.3%) were evaluated also in tissue; tissue only was analyzed in 26 cases (11.1%). Half of the tissue samples were deemed not evaluable. Druggable alterations were detected in 13 (25%) out of 52 evaluable samples and 31 of 209 (14.8%) of plasma samples. Improved outcome was observed for patients with druggable alterations if treated with matched targeted agents: they had a longer median overall survival (not reached) compared with the ones who did not start any targeted therapy (9.1 months; 95% confidence interval, 4.6–13.6; p = .046). The results of NGS testing potentially also affected the outcome of patients treated with immunotherapy. Conclusion: Systematic real‐life NGS testing showed the limit of tissue analysis in NSCLC and highlighted the potentiality of genetic characterization in plasma in increasing the number of patients who may benefit from NGS screening, both influencing the clinical decision‐making process and affecting treatment outcome. Implications for Practice: Genetic characterization of cancer has become more important with time, having had positive implications for treatment specificity and efficacy. Such analyses changed the natural history of advanced non‐small cell lung cancer (aNSCLC) with the introduction of drugs targeted to specific gene alterations (e.g., EGFR mutations, ALK and ROS‐1 rearrangements). In the field of cancer molecular characterization, the applicability of the analysis of a wide panel of genes using a high‐throughput sequencing approach, such as next‐generation sequencing (NGS), is still a matter of research. This study used NGS in a real‐world setting to systematically and prospectively profile patients with aNSCLC. The aim was to evaluate its feasibility and reliability, as well as consequent access to targeted agents and impact on clinical outcome whenever a druggable alteration was detected either in tumor tissue samples or through liquid biopsy. Abstract : The availability of targeted therapies has profoundly changed the diagnostic and therapeutic pathways in solid tumors, in particular in advanced non‐small cell lung cancer; however, limited data are available concerning the real impact of next‐generation sequencing plasma characterization in clinical practice. This article reports a real‐world experience, aiming to analyze actual effect on clinical outcome.